Extensive Reading and Changes to Reading Motivation in EFL among Slovene Primary School Pupils - Pirih, Anja (Revija za elementarno izobraževanje, 2019)
The article provides insight into the dynamics of the EFL reading motivation of a group of Slovene primary school pupils voluntarily participating in a 9-month pilot extensive reading programme in EFL and the factorscausing motivational changes. Analysis of the semi-structured interviews and book reports confirms that reading motivation in EFL is a complex and dynamic process fuelled by numerous influences, most noticeably reading materials, the influence of family members, positive attitudes towards English, and external demands, which needs to be considered when designing reading programmes and researching reading motivation.
Keywords: EFL; changes to reading motivation; extensive reading; primary school pupils; influences on EFL reading motivation